HUBUNGAN ANTARA KONDISI RUMAH SUSUN DENGAN KEPUASAN TINGGAL PENGHUNI DI KOTA SURAKARTA - Anis Yuniarta; Winny Astuti; Galing Yudana (Universitas Sebelas Maret Surakarta, 2015)
Flats built as one of the alternative solutions to problems of land acquisition which is very hard to come by. There are limitations in the management of flats in Surakarta, then the resulting problems related to the condition of flats. The research problem is how to relation between condition of flats with stay occupants satisfaction in Surakarta. The method of this study is to conduct a survey of condition of flats and make the distribution of questionnaires to residents. The analysis was performed with the scoring technique and correlation analysis. Based on the analysis, found that condition of flats which has a positive correlation to the satisfaction of the inhabitants stay the distance to shopping facilities, distance to health facilities, pollution-free, the physical condition of the road and pedestrian, access to clean water, and environmental facilities. Flats for conditions that have a negative correlation to the satisfaction of the inhabitants live the ease of transportation, distance to education, distance to services and banking, distance to government services, access to the waste water, and access to electricity. Keywords: Relation, Stay Satisfaction, Condition of Flats, Occupants, Flats